Chemerin activation in human obesity - Chang, Shwu‐Shin; Eisenberg, Dan; Zhao, Lei; Adams, Christopher; Leib, Ryan; Morser, John; Leung, Lawrence (Obesity (Silver Spring, Md.), 2016)
Objective Chemerin is an inflammatory adipokine, whose activity is regulated by successive proteolytic cleavages at its C‐terminus. It is secreted as an inactive precursor (chem163S); cleavage at Lys158 converts it to chem158K with modest activity. Chem157S is the most potent form and chem155A is inactive. The aim of this study was to determine if chemerin was activated in samples from patients with obesity. Methods Using specific ELISAs for different chemerin forms and a pan‐chemerin ELISA, chemerin forms in human obesity were characterized. Results Plasma chemerin from patients with obesity (BMI 44.3 ± 1.3 kg/m2, n = 29) was significantly higher than in lean controls (BMI 20.9 ± 0.7 kg/m2, n = 10) (160 ± 11 vs. 76.2 ± 5.5 ng/mL, respectively, P < 0.0001). This increase in chemerin was due to increased previously unattributed chemerin, with further C‐terminal truncation demonstrated by mass spectrometry, accounting for ∼35% of total plasma chemerin. Chemerin forms in adipose tissue showed a different profile, with minimal chem163S and significant levels of chem157S. Chem155A was present in omental but not in subcutaneous adipose tissue. Unattributed chemerin forms were undetectable in adipose tissue. Conclusions Chemerin is activated in adipose tissue of subjects with obesity, and further C‐terminal processing occurs during the disposition of chemerin from adipose tissue, resulting in substantial levels of novel degraded forms in plasma that correlate with obesity.